Pain in the hip joint - Yuri Aleksandrovich Olyunin (Современная ревматология, 2013)
Pathological changes that develop in the hip joints (HJ) have different origins and mechanisms of development, but their main manifestation is pain. The nature of this pain cannot be well established on frequent occasions. The English-language medical literature currently classifies such disorders as greater trochanter pain syndrome (GTPS). Its major signs are chronic pain and local palpatory tenderness in the outer part of HJ. The development of GTPS may be associated with inflammation of the synovial bursae situated in the greater tronchanter, as well as with tendinitis, myorrhexis, iliotibial band syndrome, and other local changes in the adjacent tissues or with systemic diseases. So GTPS may be characterized as regional pain syndrome that frequently mimics pain induced by different diseases, including myofascial pain syndrome, osteoarthrosis, spinal diseases, etc.